Battery structure of TOPCon battery
By forming a multi-layered silicon nitride anti-reflection film layer group, a silicon nitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group on the surface of the TOPCon battery, the problems of high reflectivity and poor passivation effect of the existing TOPCon battery are solved, and the photoelectric conversion efficiency and surface uniformity are improved.
Patent Information
- Application Number
- CN202421465407.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2034-06-25
AI Technical Summary
The existing TOPCon batteries have high reflectivity on photovoltaic cells, resulting in a decrease in photoelectric conversion efficiency, poor passivation effect, less short-wave light absorption, and serious surface chromatic aberration.
Multi-layered silicon nitride anti-reflection film layer group, silicon nitride anti-reflection film layer group and silicon oxide anti-reflection film layer group are used to form a stacked film to improve the ability to absorb light from different bands in sunlight, reduce the reflectance, and enhance the passivation effect.
The TOPCon battery's absorption of short-wave light in the sunlight is improved, reflectivity is reduced, photoelectric conversion efficiency is enhanced, and surface chromatic aberration problem is improved.
Smart Images

Figure CN222721919U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of photovoltaic cell structures, in particular to a cell structure of a TOPCon cell. Background Art
[0002] In the context of the new era of the photovoltaic industry, the development of low-cost, high-efficiency photovoltaic cells is the only way for the photovoltaic industry to continue to develop. When sunlight shines on the surface of photovoltaic cells, the reflectivity of photovoltaic cells is as high as 33%, and the light loss is large, resulting in a decrease in the carriers generated by photovoltaic cells, causing the photoelectric conversion efficiency of photovoltaic cells to decrease. Therefore, reducing the reflection of sunlight on the surface of photovoltaic cells is a necessary means to improve the photoelectric conversion efficiency of photovoltaic cells.
[0003] In the prior art, the method of reducing the reflection of sunlight on the surface of photovoltaic cells is to coat one or more layers of thin film on the surface of the photovoltaic cell. According to the principle of thin film interference, the thin film can effectively reduce the reflection of sunlight. This film is called an anti-reflection film. Silicon nitride film is widely used as an anti-reflection film in the manufacturing process of photovoltaic cells. The silicon nitride film can passivate the defects on the surface and inside the N-type silicon wafer and reduce the reflection of incident light. At present, when TOPCon cells are produced on a large scale in the market, most of them use a double-layer silicon nitride film as an anti-reflection film to expand the reflection band of the silicon nitride film and increase the absorption of sunlight. However, TOPCon cells made by the anti-reflection film of the prior art also have some problems, such as poor passivation effect, less absorption of short-wave light, and severe surface color difference. Utility Model Content
[0004] In order to solve the above technical problems, the utility model provides a battery structure of a TOPCon battery. The technical solution of the utility model is as follows:
[0005] A cell structure of a TOPCon cell comprises a passivation layer, a stacked film, a boron-doped emitter, an N-type silicon wafer, a tunneling oxide layer, a phosphorus-doped polysilicon layer, an anti-reflection film layer, a front metal electrode and a back metal electrode, wherein the boron-doped emitter, the passivation layer, the stacked film and the front metal electrode are sequentially formed on the front side of the N-type silicon wafer, and the tunneling oxide layer, the phosphorus-doped polysilicon layer, the anti-reflection film layer and the back metal electrode are sequentially formed on the back side of the N-type silicon wafer; the stacked film comprises a silicon nitride anti-reflection film layer group, a silicon oxynitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group, the silicon nitride anti-reflection film layer group is formed on the front side of the passivation layer, the silicon oxynitride anti-reflection film layer group is formed on the front side of the silicon nitride anti-reflection film layer group, the silicon oxide anti-reflection film layer group is formed on the front side of the silicon oxynitride anti-reflection film layer group, and the front metal electrode is formed on the front side of the silicon oxide anti-reflection film layer group; the refractive indices of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group decrease in sequence.
[0006] Optionally, the silicon nitride anti-reflection film layer group includes a first silicon nitride anti-reflection film layer, a second silicon nitride anti-reflection film layer and a third silicon nitride anti-reflection film layer, the silicon oxynitride anti-reflection film layer group includes a first silicon oxynitride anti-reflection film layer and a second silicon oxynitride anti-reflection film layer, and the silicon oxide anti-reflection film layer group includes a silicon oxide anti-reflection film layer; the first silicon nitride anti-reflection film layer, the second silicon nitride anti-reflection film layer, the third silicon nitride anti-reflection film layer, the first silicon oxynitride anti-reflection film layer, the second silicon oxynitride anti-reflection film layer and the silicon oxide anti-reflection film layer are sequentially formed on the front side of the passivation layer; the refractive indices of the first silicon nitride anti-reflection film layer, the second silicon nitride anti-reflection film layer, the third silicon nitride anti-reflection film layer, the first silicon oxynitride anti-reflection film layer, the second silicon oxynitride anti-reflection film layer and the silicon oxide anti-reflection film layer decrease in sequence.
[0007] Optionally, the sum of the thicknesses of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group is 68-78 nm.
[0008] Optionally, the material of the passivation layer is aluminum oxide; the material of the anti-reflection film layer is silicon nitride; and the material of the tunneling oxide layer is silicon oxide.
[0009] All the optional technical solutions mentioned above can be combined arbitrarily, and the present utility model does not provide detailed descriptions of the structures after the combinations one by one.
[0010] By means of the above scheme, the beneficial effects of the utility model are as follows:
[0011] A stacked film is formed by arranging a silicon nitride anti-reflection film layer group, a silicon oxynitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group, and then a silicon nitride anti-reflection film layer group, a silicon oxynitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group are sequentially formed on the front side of the passivation layer, and the refractive indices of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group are sequentially decreased. Compared with the double-layer silicon nitride anti-reflection film layer in the prior art, the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group in the utility model have a variety of different refractive indices, which can improve the absorption of light in different bands of sunlight, thereby improving the absorption of short-wave light in sunlight, reducing the reflectivity of the TOPCon cell, increasing the transmittance of light on the TOPCon cell, and improving the photoelectric conversion efficiency of the TOPCon cell. The utility model utilizes the low interface state density characteristics of the silicon oxynitride anti-reflection film layer to reduce the load on the surface of the TOPCon cell, enhance the passivation effect of the TOPCon cell, improve the utilization rate of light, and improve the photoelectric conversion efficiency of the TOPCon cell; compared with the double-layer silicon nitride anti-reflection film layer in the prior art, the utility model increases the number of anti-reflection film layers on the front side of the N-type silicon wafer to form a stacked film, so that the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group are more uniformly stacked on the surface of the TOPCon cell, thereby improving the problem of severe color difference on the surface of the TOPCon cell.
[0012] The above description is only an overview of the technical solution of the utility model. In order to more clearly understand the technical means of the utility model and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the utility model in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a schematic diagram of the structure of the utility model;
[0014] Figure 2 It is a schematic diagram of the structure of the laminated film in the utility model.
[0015] Description of Figure Numbers:
[0016] 1. Passivation layer; 2. Laminated film; 21. First silicon nitride anti-reflection film layer; 22. Second silicon nitride anti-reflection film layer; 23. Third silicon nitride anti-reflection film layer; 24. First silicon oxynitride anti-reflection film layer; 25. Second silicon oxynitride anti-reflection film layer; 26. Silicon oxide anti-reflection film layer; 3. Boron-doped emitter; 4. N-type silicon wafer; 5. Tunneling oxide layer; 6. Phosphorus-doped polysilicon layer; 7. Anti-reflection film layer; 8. Front metal electrode; 9. Back metal electrode. DETAILED DESCRIPTION
[0017] The following is a further detailed description of the specific implementation of the present invention in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0018] like Figure 1 and Figure 2 As shown, the battery structure of a TOPCon battery provided by the utility model includes a passivation layer 1, a laminated film 2, a boron-doped emitter 3, an N-type silicon wafer 4, a tunneling oxide layer 5, a phosphorus-doped polysilicon layer 6, an anti-reflection film layer 7, a front metal electrode 8 and a back metal electrode 9. The boron-doped emitter 3, the passivation layer 1, the laminated film 2 and the front metal electrode 8 are formed in sequence on the front side of the N-type silicon wafer 4, and the tunneling oxide layer 5, the phosphorus-doped polysilicon layer 6, the anti-reflection film layer 7 and the back metal electrode 9 are formed in sequence on the back side of the N-type silicon wafer 4; The stacked film 2 includes a silicon nitride anti-reflection film layer group, a silicon oxynitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group, the silicon nitride anti-reflection film layer group is formed on the front side of the passivation layer 1, the silicon oxynitride anti-reflection film layer group is formed on the front side of the silicon nitride anti-reflection film layer group, the silicon oxide anti-reflection film layer group is formed on the front side of the silicon oxynitride anti-reflection film layer group, and the front metal electrode 8 is formed on the front side of the silicon oxide anti-reflection film layer group; the refractive indices of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group decrease in sequence.
[0019] The utility model forms a silicon nitride anti-reflection film layer group, a silicon oxynitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group on the front side of the passivation layer 1 in sequence, and sets the refractive indices of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group to decrease in sequence. Compared with the double-layer silicon nitride anti-reflection film layer in the prior art, the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group in the utility model have a variety of different refractive indices, which can improve the absorption of light in different wavelengths of sunlight, thereby improving the absorption of short-wave light in sunlight, reducing the reflectivity of the TOPCon cell, increasing the transmittance of light on the TOPCon cell, and improving the photoelectric conversion efficiency of the TOPCon cell.
[0020] The utility model utilizes the low interface state density characteristics of the silicon oxynitride anti-reflection film layer to reduce the load on the surface of the TOPCon cell, enhance the passivation effect of the TOPCon cell, improve the utilization rate of light, and improve the photoelectric conversion efficiency of the TOPCon cell; compared with the double-layer silicon nitride anti-reflection film layer in the prior art, the utility model increases the number of anti-reflection film layers 7 on the front side of the N-type silicon wafer 4 to form a stacked film 2, so that the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group are more uniformly stacked on the surface of the TOPCon cell, thereby improving the problem of severe color difference on the surface of the TOPCon cell.
[0021] Optionally, the silicon nitride anti-reflection film layer group includes a first silicon nitride anti-reflection film layer 21, a second silicon nitride anti-reflection film layer 22 and a third silicon nitride anti-reflection film layer 23, the silicon oxynitride anti-reflection film layer group includes a first silicon oxynitride anti-reflection film layer 24 and a second silicon oxynitride anti-reflection film layer 25, and the silicon oxide anti-reflection film layer group includes a silicon oxide anti-reflection film layer 26; the first silicon nitride anti-reflection film layer 21, the second silicon nitride anti-reflection film layer 22, the third silicon nitride anti-reflection film layer 23, the first silicon oxynitride anti-reflection film layer 24, the second silicon oxynitride anti-reflection film layer 25 and the silicon oxide anti-reflection film layer 26 are formed on the front side of the passivation layer 1 in sequence; the refractive indices of the first silicon nitride anti-reflection film layer 21, the second silicon nitride anti-reflection film layer 22, the third silicon nitride anti-reflection film layer 23, the first silicon oxynitride anti-reflection film layer 24, the second silicon oxynitride anti-reflection film layer 25 and the silicon oxide anti-reflection film layer 26 decrease in sequence.
[0022] Specifically, the number of silicon nitride anti-reflection film layers in the silicon nitride anti-reflection film layer group, the number of silicon oxynitride anti-reflection film layers in the silicon oxynitride anti-reflection film layer group, and the number of silicon oxide anti-reflection film layers 26 in the silicon oxide anti-reflection film layer group can all be adjusted and optimized according to the specific requirements for the refractive index of the stacked film 2.
[0023] Furthermore, the refractive index of the first silicon nitride anti-reflection film layer 21, the second silicon nitride anti-reflection film layer 22, the third silicon nitride anti-reflection film layer 23, the first silicon oxynitride anti-reflection film layer 24, and the second silicon oxynitride anti-reflection film layer 25 in the utility model can be reflected by the ratio of nitrogen atoms and silicon atoms contained therein. When silicon atoms account for a higher proportion in the ratio, it proves that the silicon content is higher and the refractive index of the layer is higher; and the refractive index of the silicon oxide anti-reflection film layer 26 is reflected by the ratio of oxygen atoms and silicon atoms contained therein. When silicon atoms account for a higher proportion in the ratio, it proves that the silicon content is higher and the refractive index of the layer is higher.
[0024] Optionally, the sum of the thicknesses of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group is 68-78 nm.
[0025] The sum of the thicknesses of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group of the present invention is the same as the sum of the thicknesses of the double-layer silicon nitride anti-reflection film layers in the prior art. Therefore, under the same thickness as the prior art, the present invention can achieve a better passivation effect and a higher utilization rate of sunlight, thereby improving the photoelectric conversion efficiency of the TOPCon cell.
[0026] Optionally, the material of the passivation layer 1 is aluminum oxide; the material of the anti-reflection film layer 7 is silicon nitride; and the material of the tunneling oxide layer 5 is silicon oxide.
[0027] In a specific embodiment, the first silicon nitride anti-reflection film layer 21, the second silicon nitride anti-reflection film layer 22, the third silicon nitride anti-reflection film layer 23, the first silicon oxynitride anti-reflection film layer 24, the second silicon oxynitride anti-reflection film layer 25 and the silicon oxide anti-reflection film layer 26 in the utility model are all prepared by PECVD process.
[0028] The specific process of preparing the laminated film 2 in the TOPCon battery provided by the utility model is as follows:
[0029] S1, sending the graphite boat loaded with N-type silicon wafer 4 into the furnace tube of the PECVD equipment through the paddle rod, and closing the furnace door of the furnace tube after the paddle rod is withdrawn;
[0030] S2, turning on the auxiliary heating device to preheat the furnace tube with the graphite boat placed inside, so that the temperature inside the furnace tube increases;
[0031] S3, performing a leak detection process on the furnace tube that has completed the preheating process to check whether the leakage rate of the furnace tube meets the process requirements;
[0032] S4, performing a first vacuuming process on the furnace tube that has completed the leak detection process to evacuate the residual gas in the furnace tube;
[0033] S5, performing a pre-deposition treatment of the silicon nitride anti-reflection film layer group on the furnace tube that has completed the vacuum treatment, specifically: introducing silicon nitride with a gas flow rate of 2930 sccm / min and ammonia with a gas flow rate of 10450 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 210 Pa and keeping it constant, and the pre-deposition time is 20 seconds;
[0034] S6, performing a first silicon nitride anti-reflection film layer 21 deposition process on the furnace tube that has completed the pre-deposition process of the silicon nitride anti-reflection film layer group, specifically: introducing silicon nitride with a gas flow rate of 2930 sccm / min and ammonia with a gas flow rate of 10450 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 220 Pa and keeping it constant, performing a first glow discharge on the N-type silicon wafer 4 in the furnace tube through a radio frequency power supply, and the deposition time is 100 s;
[0035] S7, performing a second silicon nitride anti-reflection film layer 22 deposition process on the furnace tube that has completed the first silicon nitride anti-reflection film layer 21 deposition process, specifically: introducing silicon nitride with a gas flow rate of 2100 sccm / min and ammonia with a gas flow rate of 13570 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 220 Pa and keeping it constant, performing a second glow discharge on the N-type silicon wafer 4 in the furnace tube through a radio frequency power supply, and the deposition time is 210 s;
[0036] S8, performing a third silicon nitride anti-reflection film layer 23 deposition process on the furnace tube that has completed the second silicon nitride anti-reflection film layer 22 deposition process, specifically: introducing silicon nitride with a gas flow rate of 1400 sccm / min and ammonia with a gas flow rate of 15617 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 220 Pa and keeping it constant, performing a third glow discharge on the N-type silicon wafer 4 in the furnace tube through a radio frequency power supply, and the deposition time is 265 s;
[0037] S9, performing a second vacuuming treatment on the furnace tube after the deposition of the third silicon nitride anti-reflective film layer 23, so as to evacuate the residual gas in the furnace tube;
[0038] S10, performing a pre-deposition treatment of the silicon oxynitride anti-reflective film layer group on the furnace tube that has completed the second vacuum treatment, specifically: introducing silicon nitride with a gas flow rate of 1380 sccm / min, ammonia with a gas flow rate of 5980 sccm / min, and nitrous oxide with a gas flow rate of 8510 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 170 Pa and keep it constant, and the pre-deposition time is 20 s;
[0039] S11, performing a first silicon oxynitride anti-reflection film layer 24 deposition process on the furnace tube that has completed the pre-deposition process of the silicon oxynitride anti-reflection film layer group, specifically: introducing silicon nitride with a gas flow rate of 1380 sccm / min, ammonia with a gas flow rate of 5980 sccm / min, and nitrous oxide with a gas flow rate of 8510 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 170 Pa and keeping it constant, performing a fourth glow discharge on the N-type silicon wafer 4 in the furnace tube through a radio frequency power supply, and the deposition time is 165 s;
[0040] S12, performing a second silicon oxynitride anti-reflection film layer 25 deposition process on the furnace tube that has completed the first silicon oxynitride anti-reflection film layer 24 deposition process, specifically: introducing silicon nitride with a gas flow rate of 1035 sccm / min, ammonia with a gas flow rate of 4600 sccm / min, and nitrous oxide with a gas flow rate of 10235 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 170 Pa and keeping it constant, performing a fifth glow discharge on the N-type silicon wafer 4 in the furnace tube through a radio frequency power supply, and the deposition time is 205 s;
[0041] S13, performing a third vacuum treatment on the furnace tube after the deposition of the second silicon oxynitride anti-reflective film layer 25, to evacuate the residual gas in the furnace tube;
[0042] S14, performing a pre-deposition treatment of the silicon oxide anti-reflective film layer group on the furnace tube that has completed the third vacuum treatment, specifically: introducing silicon nitride with a gas flow rate of 1035 sccm / min and laughing gas with a gas flow rate of 13455 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 150 Pa and keep it constant, and the pre-deposition time is 15 s;
[0043] S15, performing a deposition process of the silicon oxide anti-reflection film layer 26 on the furnace tube that has completed the pre-deposition process of the silicon oxide anti-reflection film layer group, specifically: introducing silicon nitride with a gas flow rate of 1035 sccm / min and laughing gas with a gas flow rate of 13455 sccm / min into the furnace tube, while controlling the pressure in the furnace tube to reach 150 Pa and keeping it constant, performing a sixth glow discharge on the N-type silicon wafer 4 in the furnace tube through a radio frequency power supply, and the deposition time is 110 s;
[0044] S16, performing a fourth vacuuming treatment on the furnace tube after the deposition of the silicon oxide anti-reflective film layer 26 to evacuate the residual gas in the furnace tube;
[0045] S17, performing a purging process on the furnace tube that has completed the fourth vacuuming process, by introducing nitrogen gas into the furnace tube for purging;
[0046] S18, performing a fifth vacuuming process on the furnace tube that has completed the purging process to evacuate the residual gas in the furnace tube;
[0047] S19, filling the furnace tube that has completed the fifth vacuum treatment with nitrogen to restore the pressure in the furnace tube to a normal atmospheric pressure value;
[0048] S20, opening the furnace door of the furnace tube, and taking the graphite boat out of the furnace tube using a paddle, thereby completing the preparation of the laminated film 2 in the N-type silicon wafer 4.
[0049] In order to verify the beneficial effects that can be achieved by the battery structure of the TOPCon battery provided by the utility model, a comparative example and an embodiment are set up to perform battery performance tests, and the test results are compared. The comparative example is a TOPCon battery of the prior art, and the embodiment is a battery structure of the TOPCon battery provided by the utility model. The comparison results are shown in Table 1.
[0050] Table 1
[0051] efficiency Eta Uoc Isc FF Rs R IRev2 Control group 24.964 0.7271 13.453 85.42 0.0011 1355 0.0746 Experimental Group 25.039 0.7283 13.451 85.55 0.0011 1357 0.0756 Difference 0.075 0.0012 -0.002 0.13 0.0000 2 0.0010
[0052] As shown in Table 1, multiple battery performance parameters of the battery structure of the TOPCon battery provided by the utility model are improved, which further verifies the superiority of the first silicon nitride anti-reflection film layer 21, the second silicon nitride anti-reflection film layer 22, the third silicon nitride anti-reflection film layer 23, the first silicon oxynitride anti-reflection film layer 24, the second silicon oxynitride anti-reflection film layer 25 and the silicon oxide anti-reflection film layer 26 sequentially formed in the utility model as the TOPCon battery stack film 2.
[0053] In summary, the silicon nitride anti-reflection film layer group, silicon oxynitride anti-reflection film layer group and silicon oxide anti-reflection film layer group in the battery structure provided by the utility model have a variety of different refractive indices, which can improve the absorption of light in different wavelengths of sunlight, and thus improve the absorption of short-wave light in sunlight. The utility model also utilizes the low interface state density characteristics of the silicon oxynitride anti-reflection film layer to enhance the passivation effect of the TOPCon battery; the utility model forms a first silicon nitride anti-reflection film layer 21, a second silicon nitride anti-reflection film layer 22, a third silicon nitride anti-reflection film layer 23, a first silicon oxynitride anti-reflection film layer 24, a second silicon oxynitride anti-reflection film layer 25 and a silicon oxide anti-reflection film layer 26 on the front of the boron-doped emitter 3 in sequence, so that the effect of the stacked film 2 formed on the surface of the TOPCon battery is more uniform, and the problem of severe color difference on the surface of the TOPCon battery is improved; the reflectivity of the TOPCon battery prepared by the battery structure provided by the utility model is reduced, the photoelectric conversion efficiency is improved, and the anti-PID characteristics are improved.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principle of the present invention, and these improvements and modifications should also be regarded as within the protection scope of the present invention.
Claims
1. A battery structure of a TOPCon battery, characterized in that: include: A passivation layer (1), a laminated film (2), a boron-doped emitter (3), an N-type silicon wafer (4), a tunneling oxide layer (5), a phosphorus-doped polysilicon layer (6), an anti-reflection film layer (7), a front metal electrode (8) and a back metal electrode (9), wherein the front side of the N-type silicon wafer (4) is formed with a boron-doped emitter (3), a passivation layer (1), a laminated film (2) and a front metal electrode (8), and the back side of the N-type silicon wafer (4) is formed with a tunneling oxide layer (5), a phosphorus-doped polysilicon layer (6), an anti-reflection film layer (7) and a back metal electrode (9); The stacked film (2) comprises a silicon nitride anti-reflection film layer group, a silicon oxynitride anti-reflection film layer group and a silicon oxide anti-reflection film layer group, the silicon nitride anti-reflection film layer group is formed on the front side of the passivation layer (1), the silicon oxynitride anti-reflection film layer group is formed on the front side of the silicon nitride anti-reflection film layer group, the silicon oxide anti-reflection film layer group is formed on the front side of the silicon oxynitride anti-reflection film layer group, and the front metal electrode (8) is formed on the front side of the silicon oxide anti-reflection film layer group; The refractive indices of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group decrease in sequence.
2. The battery structure of a TOPCon battery according to claim 1, characterized in that: The silicon nitride anti-reflection film layer group comprises a first silicon nitride anti-reflection film layer (21), a second silicon nitride anti-reflection film layer (22) and a third silicon nitride anti-reflection film layer (23); the silicon oxynitride anti-reflection film layer group comprises a first silicon oxynitride anti-reflection film layer (24) and a second silicon oxynitride anti-reflection film layer (25); and the silicon oxide anti-reflection film layer group comprises a silicon oxide anti-reflection film layer (26); A first silicon nitride anti-reflection film layer (21), a second silicon nitride anti-reflection film layer (22), a third silicon nitride anti-reflection film layer (23), a first silicon oxynitride anti-reflection film layer (24), a second silicon oxynitride anti-reflection film layer (25) and a silicon oxide anti-reflection film layer (26) are sequentially formed on the front side of the passivation layer (1); The refractive indices of the first silicon nitride anti-reflection film layer (21), the second silicon nitride anti-reflection film layer (22), the third silicon nitride anti-reflection film layer (23), the first silicon oxynitride anti-reflection film layer (24), the second silicon oxynitride anti-reflection film layer (25) and the silicon oxide anti-reflection film layer (26) decrease in sequence.
3. A battery structure of a TOPCon battery according to claim 1 or 2, characterized in that: The sum of the thicknesses of the silicon nitride anti-reflection film layer group, the silicon oxynitride anti-reflection film layer group and the silicon oxide anti-reflection film layer group is 68-78 nm.
4. The battery structure of a TOPCon battery according to claim 1, characterized in that: The material of the passivation layer (1) is aluminum oxide; the material of the anti-reflection film layer (7) is silicon nitride; and the material of the tunneling oxide layer (5) is silicon oxide.